Genetic Predictors of Poor Prognosis in Portuguese Patients with Juvenile Idiopathic Arthritis: Data from Reuma.pt. (4th October 2015) - Mourão, Ana Filipa; Santos, Maria José; Mendonça, Sílvia; Oliveira-Ramos, Filipa; Salgado, Manuel; Estanqueiro, Paula; Melo-Gomes, José; Martins, Fernando; Lopes, Ana; Bettencourt, Bruno Filipe; Bruges-Armas, Jácome; Costa, José; et al.
Abstract : Introduction. This study aimed to assess the genetic determinants of poor outcome in Portuguese patients with juvenile idiopathic arthritis (JIA). Methods. Our study was conducted in Reuma.pt, the Rheumatic Diseases Portuguese Register, which includes patients with JIA. We collected prospectively patient and disease characteristics and a blood sample for DNA analysis. Poor prognosis was defined as CHAQ/HAQ >0.75 at the last visit and/or the treatment with biological therapy. A selected panel of single nucleotide polymorphisms (SNPs) associated with susceptibility was studied to verify if there was association with poor prognosis. Results. Of the 812 patients with JIA registered in Reuma.pt, 267 had a blood sample and registered information used to define "poor prognosis." In univariate analysis, we found significant associations with poor prognosis for allele A of TNFA1P3/20 rs6920220, allele G of TRAF1/C5 rs3761847, and allele G of PTPN2 rs7234029. In multivariate models, the associations with TRAF1/C5 (1.96 [1.17–3.3]) remained significant at the 5% level, while TNFA1P3/20 and PTPN2 were no longer significant. Nevertheless, none of associations found was significant after the Bonferroni correction was applied. Conclusion. Our study does not confirm the association between a panel of selected SNP and poor prognosis in Portuguese patients with JIA.